Import-Export, Friperie : Selected Bales : with Sam De Buysere, Miles Fischler, Axel Korban, Thor Salden, Stine Sampers, Joud Toamah ; invited by Mekhitar Garabedian. - De Bondt, Sara; Garabedian, Mekhitar (Ghent : BOEKS : KASK & Conservatorium, the school of arts of HOGENT and howest, 2023)
De Buysere, Sam ; Fischler, Miles ; Korban, Axel ; Salden, Thor ; Sampers, Stine ; Toamah, Joud
Import-Export, Friperie: Selected Bales, BOEKS, Ghent, 5 to 26 May 2023
boek